THE AESTHETICS OF RESISTANCE: AN INSTALLATION BY JOMPET KUSWIDANANTO - Walid Syarthowi Basmalah; I Wayan Adnyana; I Wayan Setem; I Wayan Karja (International Journal of Multidisciplinary Research and Literature, 2026)
This article examines how Jompet Kuswidananto formulates a counter-hegemonic aesthetics through installation works that combine spectral figures, sonic orchestration, and material icons to challenge dominant narratives of history and Javanese-Indonesian identity in the post-New Order era. The research data consist of in-depth interviews with Jompet (2024-2025), exhibition documentation, and secondary literature. The analysis focuses on Java's Machine: Phantasmagoria (2008), which presents a parade of “ghost soldiers” and hybridises marching-band sounds with Javanese symbols, and on After Voices (2016), which articulates political memory and collective movement. The findings reveal three principal counter-hegemonic aesthetic devices: (1) spectrality, which reactivates historical trauma and destabilises the authority of representation; (2) sonic-politics, which inserts irony into militaristic and nationalist forms of discipline; and (3) symbolic iconoclasm, exemplified by the use of crystal chandeliers as allegories for the collapse of colonial power. Drawing upon Antonio Gramsci's theory of hegemony, Stuart Hall's concept of representation, and Claire Bishop's writings on installation art, this study demonstrates that Jompet’s works create a space for negotiating meaning, enriching the discourse of contemporary art in Southeast Asia. This article contributes to cultural studies by proposing the “Three S” matrix (spectrality, sonic politics, and symbolic iconoclasm) as an analytical framework for examining counter-hegemonic strategies in installation art